A new high yielding and high oil content Indian mustard variety 'GM 6' (Banas Sona) recommended for Gujarat state: A NEW HIGH YIELDING AND OIL CONTENT INDIAN MUSTARD VARIETY 'GM 6' - K P PRAJAPATI; J R PATEL; S K SHAH; G P GANGWAR; D N TEJANI; A L JAT; B K PATEL; A G DESAI (Journal of Oilseeds Research, 2021)
A high yielding genotype of Indian mustard SKM 1328 was evolved from cross between IC 385682 and SKM 0820 at Castor-MustardResearchStation, Sardarkrushinagar DantiwadaAgricultural University, Sardarkrushinagar and identified for release as Gujarat Mustard 6 (Banas Sona) for Gujarat state. The genotype SKM 1328 was identified owing to its superior performance in preliminary yield trial conducted at Sardarkrushinagar during 2013-14. It was evaluated in multi location trials from 2014-15 to 2018-19, simultaneously it was screened against aphid and powdery mildew under late sown epiphytotic conditions at Sardarkrushinagar. Under AICRP trial, it was tested under Initial Varietal Trial (Timely sown, irrigated) at four different centres of zone IV in the year 2017-18. The mean seed yield of GM 6 (Banas Sona) variety under timely sown irrigated condition in Gujarat state was 2541 kg/ha with an increase of 14.20, 13.98 and 11.94 per cent over the check varieties Kranti, GM 3 and GDM 4, respectively. Under limited irrigation conditions, GM 6 recorded 1758 kg/ha of seed yield which was 8.85, 27.21, 9.85 and 17.75 per cent higher over the check varieties Kranti, GM 1, GM 3 and GDM 4, respectively. It was also found superior in quality traits. It recorded high oil content (38.89 %) with oil yield of 988 kg/ha which was 20.34, 24.75 and 15.02 per cent higher as compared to the check varieties Kranti, GM 3 and GDM 4, correspondingly. Besides, it also possessed comparatively high oleic acid (12.51%) than the check varieties. It has higher 1000 seed weight (5.66 g) as compared to all three checks except GM 3 which recorded 5.72 g 1000 seed weight. Considering the average seed yield in irrigated as well as limited irrigated condition and quality of the genotype SKM 1328, it was proposed and identified for release as Gujarat Mustard 6 (Banas Sona) for general cultivation by mustard growing farmers of Gujarat state.